Hydrophilic trans-cyclooctenylated noncanonical amino acids for fast intracellular protein labeling - Kozma, Eszter; Nikić, Ivana; Varga, Balázs R.; Aramburu, Iker Valle; Kang, Jun Hee; Fackler, Oliver Till; Lemke, Edward A.; Kele, Péter (ChemBioChem, 2016)
Abstract Introduction of bioorthogonal functionalities (e.g., trans-cyclooctene-TCO) into a protein of interest by site-specific genetic encoding of non-canonical amino acids (ncAAs) creates uniquely targetable platforms for fluorescent labeling schemes in combination with tetrazine-functionalized dyes. However, fluorescent labeling of an intracellular protein is usually compromised by high background, arising from the hydrophobicity of ncAAs; this is typically compensated for by hours-long washout to remove excess ncAAs from the cellular interior. To overcome these problems, we designed, synthesized, and tested new, hydrophilic TCO-ncAAs. One derivative, DOTCO-lysine was genetically incorporated into proteins with good yield. The increased hydrophilicity shortened the excess ncAA washout time from hours to minutes, thus permitting rapid labeling and subsequent fluorescence microscopy.
Gesehen am 25.05.2020